Interreligious Environmental Ethics: A Comparative Philosophical Analysis of Religious Teachings and Ecological Responsibility - Mahfud Heru Fatoni; Muhamad Hanif Fuadi; Adhe Ismail Ananda; Mamdukh Budiman (International Forum of Researchers and Lecturers, 2024)
This study explores the role of interreligious environmental ethics in shaping global cooperation to address the ongoing ecological crisis. By analyzing and comparing the teachings of Islam, Christianity, Hinduism, and Buddhism, the study identifies key environmental ethics principles that are shared across these religious traditions, such as non-violence, the sacredness of nature, and the principle of moderation in resource use. Despite theological and doctrinal differences, these shared values provide a strong philosophical and moral foundation for fostering cooperation among religious communities in addressing global environmental challenges. The study also examines the philosophical divergences within religious teachings, such as the varying interpretations of human dominion over nature and the role of humans as stewards or caretakers of the Earth. These theological differences present challenges in creating a unified environmental ethical framework, yet they also highlight the richness and diversity of religious perspectives on ecological responsibility. The practical applications of these teachings are discussed, focusing on how religious values have been integrated into real-world environmental movements, such as faith-based environmentalism and interfaith collaborations. The findings underscore the potential for interfaith dialogue to catalyze global environmental action and the creation of a unified global ethical system. Such a system, grounded in shared religious values, could provide a framework for sustainable practices and ecological justice, offering a moral guide for individuals, communities, and nations in their efforts to mitigate environmental degradation and promote sustainability.